Study and interpretation of wall graffiti on boats in Catalonia from antiquity to the present: a novel project (Salduie, 2022)
In this research article we present the project that we are carrying out, and the applied methodology that we have developed, for the study of the parietal graffiti of boats in the continental Cataluña, from ancient times to the contemporary world. This corpus is part of a line of research of the Maritime Museum of Barcelona and the Permanent Observatory of Maritime History and Culture of the Mediterranean, being a novel research project through which we try, beyond his study, to revalue and make a determined defense of the need to conserve and value this heritage.
Keywords: Heritage; Folk art; Naval architecture; Graffiti; Scariphare